2021
DOI: 10.1007/s00766-021-00355-3
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies information systems

Abstract: This article introduces a new class of socio-technical systems, interspecies information systems (IIS) by describing several examples of these systems emerging through the use of commercially available data-driven animal-centered technology. When animal-centered technology, such as pet wearables, cow health monitoring, or even wildlife drones captures animal data and inform humans of actions to take towards animals, interspecies information systems emerge. I discuss the importance of understanding them as info… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 107 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…Particularly where the expected benefit of a technological intervention is the protection of their privacy and the enablement of their privacy management strategies, control over such interventions ought to be shared with animal stakeholders. In other words, animal stakeholders should be able to influence the behaviour of the technology and of its human users, such that systems' impact was bi-directional-to use a term proposed by van der Linden (54). Thus, as far as possible, technological interventions could be designed to enable animals to asses said contingencies and to allow them to dissent, such that their dissent impacts the behaviour of the technology and of its human users.…”
Section: The Paradox Of Using Technology To Protect Animals' Privacymentioning
confidence: 99%
“…Particularly where the expected benefit of a technological intervention is the protection of their privacy and the enablement of their privacy management strategies, control over such interventions ought to be shared with animal stakeholders. In other words, animal stakeholders should be able to influence the behaviour of the technology and of its human users, such that systems' impact was bi-directional-to use a term proposed by van der Linden (54). Thus, as far as possible, technological interventions could be designed to enable animals to asses said contingencies and to allow them to dissent, such that their dissent impacts the behaviour of the technology and of its human users.…”
Section: The Paradox Of Using Technology To Protect Animals' Privacymentioning
confidence: 99%
“…[5][p. 50] That is, Bannon also tells us to not a priori consider technology a solution, nor that focusing on technical user-centeredness (i.e., usability and ergonomics) will offer us the answers we seek. We need to initiate a "bottom-up process of rediscovering our human potential and reconstructing the very foundations" Reimagining HCI, he concludes, is about encouraging "an openness to new forms of thinking about the humantechnology relationship"-an even more complicated matter when animals become involved in a human-animal-technology triadic relationship [39].…”
Section: What Animal-centered Ought To Mean In Acimentioning
confidence: 99%
“…Pet tech is an umbrella term for the category of products and services designed to better the health and well-being of our pets [3], with 'dog tech' similarly being such products tailored towards dogs (and their human caregivers). These technologies range from software, consumer grade hardware, and even industrial grade solutions used by veterinarians and other animal professionals, frequently based around collecting and interpreting data to help inform caregivers on an animal's behavioural and/or physiological condition [3]-effectively giving rise to an 'interspecies information system' [31] where human caregivers are given processed animal data to act upon. ACI research as a result is inherently linked to the design and development of such technology, being focused on improving our understanding of how animals live in their environments, and how we can live together better [18].…”
Section: Dog Tech (And Privacy)mentioning
confidence: 99%
“…Within ACI, the focus of Dog-Computer Interaction (DCI) in particular provides important cues to understanding the importance of proper design of dog tech, whether that is for dog-human or dog-dog interactions [12]. DCI interactions effectively provide a means of interspecies data collection that can subsequently be acted upon [31], and has focused on tech such as monitoring and tracking dogs [16], training them [20], improving their working functions [23], collect information about their physiology [17], or simply playing games and having fun [5]. ACI/DCI research has shown how appropriate use of certain dog tech can help raise quality of life for dogs by giving allowing their caregivers to tailor their care and behaviour towards the dog [28,37].…”
Section: Dog Tech (And Privacy)mentioning
confidence: 99%